PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAERAH KABUPATEN PAMEKASAN - Kinta Alfia Daniati; C. Sri Hartati; Chamariyah Chamariyah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to determine and analyze the simultan and partial influence of transformational leadership, motivation and work environment on the employees performance of Badan Keuangan Daerah Kabupaten Pamekasan and to know which variables have a dominant influence on the employees performance of Badan Keuangan Daerah Kabupaten Pamekasan. This study uses primary data obtained by spreading the questionnaires to employees of Badan Keuangan Daerah Kabupaten Pamekasan. The sample in this study amounted to 60 employees. Sampling is done by using census method and data testing technique used in this research include validity test, reliability test and multiple regression analysis. The results showed that transformational leadership, motivation and work environment have a significant influence simultaneously and partially on the employees performance of Badan Keuangan Daerah Kabupaten Pamekasan. Motivation has a dominant influence on the employees performance of Badan Keuangan Daerah Kabupaten Pamekasan. Keywords: transformational leadership, motivation, work environment, employee performance